2017
DOI: 10.3184/174751917x15021050367558
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo-Natural Products, Some Artefacts Formed during the Isolation of Terpenoids

Abstract: The formation of artefacts during the isolation, purification and characterisation of terpenoids is reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…Although few, there has been some reports on natural occurring triterpenoidal acetonides from plants [ 17 – 19 ]. Despite the fact that 1 is considered unusual being an acyclic acetonide ketal, it is assumed to be an artifact derived from phytolaccagenic acid 3 β - O -myristate ( 1a ) during the chromatographic process, in which acetone was used as solvent [ 20 , 21 ]. The proposed mechanism in the formation of 1 from 1a involves firstly a nucleophilic attack of the C-23 hydroxyl to a protonated acetone molecule, followed by an intramolecular nucleophilic substitution at the fatty acid carbonyl at C-3 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although few, there has been some reports on natural occurring triterpenoidal acetonides from plants [ 17 – 19 ]. Despite the fact that 1 is considered unusual being an acyclic acetonide ketal, it is assumed to be an artifact derived from phytolaccagenic acid 3 β - O -myristate ( 1a ) during the chromatographic process, in which acetone was used as solvent [ 20 , 21 ]. The proposed mechanism in the formation of 1 from 1a involves firstly a nucleophilic attack of the C-23 hydroxyl to a protonated acetone molecule, followed by an intramolecular nucleophilic substitution at the fatty acid carbonyl at C-3 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…They vary from simple esterification, solvolysis and oxidation to highly complex chemical rearrangements. Artifact formation of various terpenoids was reviewed by Hanson (2017) . Dehydration, rearrangements, and oxidation, among others, cause formation of artifacts from all kinds of terpenes.…”
Section: Solvents For Extraction and Chromatographymentioning
confidence: 99%
“…One of the main problems encountered during their manipulation and study is linked to their chemical instability; this has a significant impact both on their initial detection/identification and on the accuracy of their analytical characterization. Many natural biomolecules and metabolites are highly reactive compounds; consequently, they can potentially lead to artifacts’ formation during their isolation, purification and characterization [ 1 ]. In his review [ 1 ], Hanson reported a list of the main mechanisms often resulting in artifacts, which include dehydration [ 2 ], rearrangement [ 3 ] and oxidation reactions [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many natural biomolecules and metabolites are highly reactive compounds; consequently, they can potentially lead to artifacts’ formation during their isolation, purification and characterization [ 1 ]. In his review [ 1 ], Hanson reported a list of the main mechanisms often resulting in artifacts, which include dehydration [ 2 ], rearrangement [ 3 ] and oxidation reactions [ 4 ]. In addition, once in contact with organic solvents, NPs may be subjected to chemical transformations which can alter their odorous, appearance, and even biological properties [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation